Impact of encapsulating a probiotic (Pediococcus pentosaceus Li05) within gastro-responsive microgels on Clostridium difficile infections. Issue 7 (18th March 2021) - Xie, Jiaojiao; Yao, Mingfei; Lu, Yanmeng; Yu, Mengjia; Han, Shengyi; McClements, David J.; Xiao, Hang; Li, Lanjuan
Abstract : Encapsulated Li05 within a gastro-responsive microgel controlled release in intestine and enhanced its efficacy against CDI. Abstract : Antibiotic treatment is often followed by Clostridium difficile infection (CDI), which causes severe diarrhea and other health issues. Oral administration of Pediococcus pentosaceus Li05 (Li05) has been shown to have great potential in preventing CDI. However, the viability of Li05 is greatly reduced during storage and passage through the gastrointestinal (GI) tract, which limits its biological activity. In this study, a gastro-responsive microgel was designed to encapsulate and protect Li05 to enhance its efficacy against CDI. The viability of Li05 encapsulated within the microgels was significantly enhanced during long-term storage and after exposure to simulated GI fluids. Moreover, this gastro-responsive microgel led to greater sustained release of the probiotic. In a mouse CDI model, we found that encapsulated Li05 was better at inhibiting C. difficile infection than nonencapsulated Li05, as demonstrated through analysis of the probiotic survival rate, spleen weight, colonic histology, and inflammatory cytokine levels. Moreover, the gut microbial diversity was enriched by treatment with encapsulated Li05. These results suggest that encapsulating Li05 within biopolymer microgels may enhance its ability to prevent and treat CDI using functional foods, supplements, or pharmaceuticals.